Sex difference and immunosenescence affect transplantation outcomes - Maenosono, Ryoichi (Frontiers in Transplantation, 2023)
Kidney transplantation is a well-established alternative to renal replacement therapy. Although the number of patients with end-stage renal disease (ESRD) is increasing, the availability of kidney for transplantation is still insufficient to meet the needs. As age increases, the prevalence of ESRD increases; thus, the population of aged donors and recipients occupies large proportion. Accumulated senescent cells secrete pro-inflammatory factors and induce senescence. Additionally, it is gradually becoming clear that biological sex differences can influence aging and cause differences in senescence. Here, we review whether age-related sex differences affect organ transplant outcomes and what should be done in the future.